APPLICATION OF THINK PAIR SHARE MODEL ASSISTED BY SITUATION CARDS TO IMPROVING CRITICAL THINKING SKILLS OF JUNIOR HIGH SCHOOL STUDENT - Titin Pujianti; Alim Salamah; Jamil; Fitri Nur Handayani (SOSIOEDUKASI, 2025)
The lack of direct involvement of students in learning activities, plus the use of conventional teaching methods by teachers to date, causes limitations on students’ critical thinking. This research is intended to explore the effectiveness of the application of the Think Pair Share model assisted by situation cards in improving the critical thinking skill of grade VIII junior high school student related to the material “National Cultural Challenges in the Era of Globalization”. This study applies a pre-experimental type of One Group Pretest-Posttest, with a sample of 34 students in class VIII-11 of SMP Negeri 4 Samarinda who were freely selected. The instruments utilized were pre-test and post-test essay tests and student involvement observation instruments. The findings in this study were analyzes statistically through a descriptive analysis approach and the Paired Sample t-Test. The findings indicated that there was a significant difference between the pre-test mean score of 48.32, increasing to 83.21 after the implementation of the post-test. The normality test of the data was identified as normally distributed, and the t-test showed a significance of 0.001 <0.05, indicating a significant difference between before treatment and after treatment. Based on this research, it is proven that the application of the Think Pair Share model assisted by situation has an impact on improving student’s critical thinking skills.